Experimental Determination of Wind‐Induced Response on a Model of Natural Draught Cooling Tower. Issue 1 (23rd March 2011) - Babu, G. Ramesh; Rajan, S. Selvi; Harikrishna, P.; Lakshmanan, N.; Arunachalam, S.
<x xml:space="preserve">Abstract</x> The detailed and well‐publicized documented paper by Bamu and Zingoni in 2005 on cooling‐tower collapses accentuates the effect of wind on the performance of cooling towers. As it is well established that wind‐tunnel tests on tower models result in a more realistic assessment of wind‐induced stresses, wind‐tunnel tests are conducted on aero‐elastic model of an isolated cooling tower and the cooling tower with surrounding structures. The details of the experimental programme, measurements, analysis, and results for both the isolated and interference cases are presented in this paper. Based on the analysis of experimental data, ring‐resonance frequencies, and mode shapes of the model, meridional (N) and hoop (N) stress resultants and interference factor due to the presence of surrounding buildings are evaluated. The values of N, N, ring‐resonance frequencies, and mode shapes for isolated model are further compared with the values obtained based on finite element analysis.